The role of external audit in combating digital financial crime - A critical outlook on the professional and global arena- - saidani, mohammed Said; zergoune, Omar farouk; bekiri, djameleddine (Journal of Excellence for Economics and Management Research, 2023)
Cybercrimes as a technology disease are spreading very speedily in present era. Nothing is secure now and institutions are under a great threat. The cost of fraud continues to be a problem for many organizations in the global economy. This study explores how external audit may offer a way forward for organizations to reduce fraud and advance organizational audit effectiveness for detecting potential fraud areas and cases. the access to evidence is increasingly more complex and in far greater volumes than in previous decades. The research results offer more open-ended questions and opportunities to develop and upgrade this specific area, There needs to be the development of automated and specialist problem-solving auditing software and secondly, the new skills required by auditors to be effective in an intelligent workplace.